Assessment of knowledge, attitude, and practice of dog owners to rabies disease in Kahama town council, Shinyanga region, Tanzania. - Shabani Iddi; Farida Mlenga; Kayo Hamasaki; Stanley Mwita; Eveline Konje (Public Library of Science (PLoS), 2023)
Background Rabies is a fatal zoonotic disease of significant public health importance. Domestic dogs are the main reservoir and transmitter of this disease, particularly in developing countries. Community awareness about rabies is one of the key components of prevention. This study describes the knowledge, attitudes, and practices about rabies disease among dog owners at Kahama town council, Shinyanga Region, Tanzania. Methodology This was a cross sectional community-based study which was done in May 2021. Structured questionnaires were administered to collect the data among 422 dog owners. The information collected included demographic characteristics of the dog owners, as well as their knowledge, attitude and practice towards rabies. Data were analyzed using SPSS statistical software version 20. Results Out of 422 respondents, 421 (99.76%) knew that rabies can be transmitted by dogs, 384 (91%) knew that rabies can be prevented by vaccination of dogs, 269 (63.74%) knew the symptoms and signs, and 379 (89.81%) believed that it was necessary to vaccinate all owned dogs, but 227 (53.79%) had not vaccinated their dogs. Education level (p = 0.006) and occupation (p = 0.002) were significantly associated with a positive attitude, whereby those with a higher level of education and farmers were more likely to have a positive attitude. Also there was statistically significant association between gender (p = 0.038), marital status (p < 0.001) occupation (p < 0.001), education level (p = 0.006) and the practices of the respondents in the community whereby majority of male, unmarried dog owner who are farmer with primary education level had lower practice score. Conclusion This study concludes that respondents had good knowledge, a relatively good attitude, and poor practice towards rabies prevention and control. Rabies awareness with an emphasis on the importance of vaccination as well as vaccination campaigns should, therefore, be intensified, especially among the least educated dog owners.